The Influence of Audiovisual Media on Understanding Concepts and Social Skills in Social Studies Learning in Elementary School Students - Tugimin; Nurmalina; Imam Hanafi (Institute of Educational, Research, and Community Service, 2024)
This study aims to determine the influence of audiovisual media on concept understanding and social skills in Social Studies (IPS) learning for sixth-grade students at SD Negeri 9 Tanjunggemuk. Audiovisual media was chosen for its ability to present information in an engaging and interactive manner, thereby enhancing students' concept understanding and social skills. The research method used is an experiment with a pretest-posttest control group design. The research sample consists of two classes: the experimental class using audiovisual media and the control class using conventional methods. Data were collected through tests on concept understanding and social skills. Data analysis employed the Mann-Whitney test to observe differences between the experimental and control groups. The results show that the use of audiovisual media significantly improves students' concept understanding and social skills compared to conventional methods. The Mann-Whitney test results indicate a significant difference between the experimental and control groups in terms of concept understanding and social skills. Therefore, audiovisual media can be considered an alternative in Social Studies learning to enhance the quality of education in elementary schools.